Antimicrobial peptides from the skin of the Japanese mountain brown frog Rana ornativentris: Evidence for polymorphism among preprotemporin mRNAs - Ohnuma, Aya; Michael Conlon, J.; Yamaguchi, Keiko; Kawasaki, Hiroaki; Coquet, Laurent; Leprince, Jérôme; Jouenne, Thierry; Vaudry, Hubert; Iwamuro, Shawichi (Peptides (New York, N.Y. : 1980), 2007)
A previous study led to the isolation of antimicrobial peptides belonging to the temporin and brevinin-2 families from a pooled extract of the skin of adult specimens of the Japanese mountain brown frog Rana ornativentris Werner 1903. In order to ascertain whether individual frogs expressed the full complement of temporin genes, we individually cloned cDNAs encoding the temporin precursors from total RNA extracted from the skins of 12 frogs by RT-PCR using a set of preprotemporin-specific primers. All the specimens examined contained mRNAs directing the synthesis of the novel, but inactive, temporin-1Oe (ILPLLGNLLNGLL·NH 2). Nucleotide sequence analysis revealed marked polymorphism among individual frogs. Twenty-seven distinct preprotemporin-1Oe mRNAs were identified that contained synonymous substitutions in the antimicrobial peptide region and both synonymous and non-synonymous substitutions in the signal peptide and intervening sequence regions. Up to eight preprotemporin-1Oe mRNA variants were found within a single frog. In addition, several cDNAs encoding preprotemporin-1Oa and -1Ob and a single cDNA encoding preprotemporin-1Oc were characterized. Peptidomic analysis of norepinephrine-stimulated skin secretions revealed the presence of temporin-1Oe, temporin-1Of (SLILKGLASIAKLF·NH 2), temporin-1Og (FLSSLLSKVVSLFT·NH 2), four members of the ranatuerin-2 family and one member of the palustrin-2 family in addition to previously characterized temporin and brevinin-2 peptides.